Fundamentalne determinanty modelowania inwestycji kapitałowych - Urbański, Stanisław (Fundamental Determinants of the Capital Investments Simulation, 2006)
The research carried out in the world in the nineties has shown that the future rates of return are determined first of all by the structure of the profits which significantly influences the parameters of the company evaluation such as the profit to market value ratio. The present paper presents the research concerning the optimization of the parameters allowing the creation of the portfolios among the companies in the best condition by the end of the current reporting period from the market point of view. In order to do that the fundamental model of the securities portfolio management based on the objective function maximization dependet on the structure of the profits and the value of the company evaluation parameters has been applied. Depending on the form of the assumed explanatory variables and their importance determining the values of the objective functions there are generated the portfolios which are the different combinations of the selected securities, respectively evaluated by the market in the future period.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 647-659